Development of hybrid anti-islanding based on distributed generation interconnection - Abdolrasol, M.G.M.; Mekhilef, Saad (Praise Worthy Prize, 2012)
The proposed method is a combination of two detection methods, namely, the active and passive islanding detection methods. The former generates disturbances at the output of the distributed generation by the use of both positive and continuous feedback signal injection which is based on DQ implementation, while the latter is based on measuring the system parameters such as voltage, frequency, active and reactive power and total harmonic distortion (THD). The grid and the distributed generation (DG) connected in parallel by three-phase RLC load. Test the performance of the technique with and without the anti-islanding controller. This method could detect the islanding situations in a very short time reach to 0.8sec. Possible islanding conditions are simulated and verified with full simulation analysis and excremental results.